A new approach to measuring individual differences in sensitivity to facial expressions: influence of temperamental shyness and sociability - Gao, Xiaoqing; Chiesa, Julia; Maurer, Daphne; Schmidt, Louis A. (Frontiers in Psychology, 2014)
To examine individual differences in adults’ sensitivity to facial expressions, we used a novel method that has proved revealing in studies of developmental change. Using static faces morphed to show different intensities of facial expressions, we calculated two measures: (1) the threshold to detect that a low intensity facial expression is different from neutral, and (2) accuracy in recognizing the specific facial expression in faces above the detection threshold. We conducted two experiments with young adult females varying in reported temperamental shyness and sociability - the former trait is known to influence the recognition of facial expressions during childhood. In both experiments, the measures had good split half reliability. Because shyness was significantly negatively correlated with sociability, we used partial correlations to examine the relation of each to sensitivity to facial expression. Sociability was negatively related to threshold to detect fear (Experiment 1) and to misidentify fear as another expression or happy expressions as fear (Experiment 2). Both patterns are consistent with hypervigilance by less sociable individuals. Shyness was positively related to misidentification of fear as another emotion (Experiment 2), a pattern consistent with a history of avoidance. We discuss the advantages and limitations of this new approach for studying individual differences in sensitivity to facial expression.